Answer:
Explanation:
The <em>average</em> is the mean. It is calculated adding all the values and dividing the sum by the number of values (data):
For the students who took the test the day before you, you can write:
![mean_1=\sum scores/n](https://tex.z-dn.net/?f=mean_1%3D%5Csum%20scores%2Fn)
Where n is the number of students who took the test first.
Thus, when the average was 69 the equation is:
![69=\sum scores/n](https://tex.z-dn.net/?f=69%3D%5Csum%20scores%2Fn)
When you take the test, the n + 1, the new average is 70, and the sum of the scores raised in 95 points:
![mean_2=(\sum scores + 95)/(n+1)\\ \\ 70=(\sum scores+95)/(n+1)](https://tex.z-dn.net/?f=mean_2%3D%28%5Csum%20scores%20%2B%2095%29%2F%28n%2B1%29%5C%5C%20%5C%5C%2070%3D%28%5Csum%20scores%2B95%29%2F%28n%2B1%29)
Now you have a system of two equation and two unknowns, so you can solve it.
Clear the sum of the scores from the first equation:
![69=\sum scores/n=>\sum scores=69n](https://tex.z-dn.net/?f=69%3D%5Csum%20scores%2Fn%3D%3E%5Csum%20scores%3D69n)
Subsitute in the second equation:
![70=(69n+95)/(n+1)](https://tex.z-dn.net/?f=70%3D%2869n%2B95%29%2F%28n%2B1%29)
Solve for n:
![70(n+1)=69n+95\\ \\ 70n+70=69n+95\\ \\ 70n-69n=95-70\\ \\ n=25](https://tex.z-dn.net/?f=70%28n%2B1%29%3D69n%2B95%5C%5C%20%5C%5C%2070n%2B70%3D69n%2B95%5C%5C%20%5C%5C%2070n-69n%3D95-70%5C%5C%20%5C%5C%20n%3D25)
Thus, when you include your self the number of students who took the test was 25 + 1 = 26.